2019
DOI: 10.1158/1078-0432.ccr-18-1319
|View full text |Cite
|
Sign up to set email alerts
|

A CK1α Activator Penetrates the Brain and Shows Efficacy Against Drug-resistant Metastatic Medulloblastoma

Abstract: Purpose: Although most children with medulloblastoma are cured of their disease, Sonic Hedgehog (SHH) subgroup medulloblastoma driven by TRP53 mutations is essentially lethal. Casein kinase 1a (CK1a) phosphorylates and destabilizes GLI transcription factors, thereby inhibiting the key effectors of SHH signaling. We therefore tested a secondgeneration CK1a activator against TRP53-mutant, MYCNamplified medulloblastoma.Experimental Design: The ability of this CK1a activator to block SHH signaling was determined i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…Casein kinase 1α (CK1α), encoded by CSNK1A1 , is a classical negative regulator for the Wnt/β-catenin signaling pathway ( 14 ). In addition to Wnt/β-catenin signaling, CK1α also regulates p53, GLI transcription factors and other important signaling pathways ( 15 17 ). CK1α has been reported to be implicated in apoptosis, survival, senescence and other cellular physiological processes, thus regulating the occurrence and development of multiple tumors ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Casein kinase 1α (CK1α), encoded by CSNK1A1 , is a classical negative regulator for the Wnt/β-catenin signaling pathway ( 14 ). In addition to Wnt/β-catenin signaling, CK1α also regulates p53, GLI transcription factors and other important signaling pathways ( 15 17 ). CK1α has been reported to be implicated in apoptosis, survival, senescence and other cellular physiological processes, thus regulating the occurrence and development of multiple tumors ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Wnt/β-catenin signaling, CK1α also regulates p53, GLI transcription factors and other important signaling pathways ( 15 17 ). CK1α has been reported to be implicated in apoptosis, survival, senescence and other cellular physiological processes, thus regulating the occurrence and development of multiple tumors ( 17 , 18 ). Recently, CK1α was reported to act as a key negative regulator of oncogenic RAS-induced autophagy, suggesting that targeting CK1α-regulated autophagy provides a promising therapeutic opportunity to treat oncogenic RAS-driven cancers ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was previously demonstrated that pyrvinium and SSTC3 could also inhibit the growth of Sonic Hedgehog-driven (Shh-driven) medulloblastoma [129,134]. Even though CK1α can regulate both Shh and Wnt pathways, both CK1α activators attenuate Shh activity without affecting Wnt signaling in these medulloblastoma models [129,134]. This suggests that the primary function of these drugs is not limited to Wnt inhibition and is likely context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…SSTC3, but not its structural analog SSTC111 ( Figure 4 A), inhibits the growth of Wnt-driven CRC cell lines and patient-derived CRC organoids ex vivo [ 97 ]. Consistent with its improved bioavailability, SSTC3 remains in plasma for 24 h after intraperitoneal injection in mice and is able to penetrate the blood-brain barrier [ 97 , 129 ]. Furthermore, SSTC3 significantly inhibits the growth of primary and metastatic tumors that develop from patient CRCs or a Wnt-driven CRC cell line implanted in mice [ 97 ].…”
Section: Ck1α Activatorsmentioning
confidence: 99%
“…Recently, SSTC3 has been described as a second-generation of CK1α activator. The compound inhibits HH signaling both in vitro and in vivo and possess improved pharmacokinetic and antioncogenic properties (crossing the BBB, attenuating the growth and metastases of SHH-MB mouse models and prolonging their survival) compared to pyrvinium [124]. Most importantly, SSTC3 is effective against an orthotopically implanted SHH-MB PDX with a TRP53 mutation and MYCN amplification [124].…”
Section: Ck1α Agonistmentioning
confidence: 99%